A method for preparing a lignin-based adsorbent that can be rapidly formed at low temperature

By using sodium lignin sulfonate and acrylic acid to perform chelation reaction under low temperature conditions, combining acrylamide and zinc chloride to form a metal bridge, the problem of crosslinking agent and high temperature in the synthesis of lignin-based hydrogels in the prior art is solved. , achieves rapid molding and efficient adsorption effects.

CN117920148BActive Publication Date: 2024-12-31INNER MONGOLIA AGRICULTURAL UNIVERSITY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410109414.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-26
Publication Date
2024-12-31
Estimated Expiration
2044-01-26

AI Technical Summary

Technical Problem

The synthesis of existing lignin-based hydrogels requires crosslinking agents and higher temperatures and longer time, resulting in increased time costs and energy consumption.

Method used

The lignin-based adsorbent was prepared by chelating reaction under 25-30°C, and acrylic acid was used to form a metal bridge using acrylamide and zinc chloride to achieve rapid molding.

Benefits of technology

Without adding crosslinking agent, rapid polymerization produces lignin-based adsorbents with good mechanical properties and adsorption properties, reducing reaction time and energy consumption and increasing adsorption amount.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117920148B_ABST
    Figure CN117920148B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a lignin-based adsorbent that can be rapidly formed at low temperature, and belongs to the technical field of chemical energy. Specifically, acrylic acid and acrylamide are added to sodium lignin sulfonate, and the mass ratio of acrylic acid to acrylamide is (2-5): (0-1.2). The invention strictly controls the usage ratio of acrylic acid and acrylamide, so that the invention can prepare a lignin-based adsorbent using sodium lignin sulfonate as a raw material without adding a cross-linking agent. In addition, the invention also adds zinc chloride to the raw material, and the zinc chloride forms a metal bridge under the chelation action of sodium lignin sulfonate and acrylic acid, thereby obtaining a new lignin-based adsorbent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical energy, and in particular relates to a method for preparing a lignin-based adsorbent that can be quickly formed at low temperature. Background Art

[0002] There are many methods for preparing lignin-based hydrogels. Generally speaking, the synthesis of hydrogels using lignin includes interpenetrating polymer networks and polymerization, cross-linking copolymerization, and cross-linking grafting of lignin and monomers. In most methods, cross-linking agents are used as raw materials, and the reaction process is basically accompanied by heating and a long reaction time. This increases the time cost and energy consumption to a certain extent.

[0003] Shao-FeiSun et al. developed an economical and environmentally friendly lignin-based network composite hydrogel adsorbent (PAA@SML) using polyacrylic acid (PAA) and thiomethylated lignin (SML) as raw materials through free radical polymerization and crosslinking, which was used to adsorb methylene blue. Its maximum theoretical adsorption capacity is 777.1 mg·g -1 In the reaction process, an initiator (KPS) and a cross-linking agent (NMBA) were added, and the synthesized lignin-based network composite hydrogel needed to react at 60°C for 3 hours.

[0004] Xiao-Feng Sun et al. developed a super absorbent hydrogel for removing Cu(II) ions using lignin and acrylic acid (AA) as raw materials and montmorillonite as a reinforced composite material for adsorbing Cu in water. 2+ The maximum theoretical adsorption capacity is 1.17 mmol·g -1 The reaction process also uses a cross-linking agent (MBA). Summary of the invention

[0005] The synthesis of existing lignin-based hydrogels basically requires the use of cross-linking agents, and relatively high temperatures and long times are required. Some syntheses even require ultrasound assistance and ultraviolet irradiation, which to a certain extent increases the time cost and energy consumption. To address this problem, the present invention proposes a method for preparing a lignin-based adsorbent that can be quickly formed at low temperatures.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing a lignin-based adsorbent that can be quickly formed at low temperature, wherein sodium lignin sulfonate and acrylic acid are used as raw materials, and acrylamide is added at 25-30°C to produce a chelating reaction to prepare the adsorbent; the amount of acrylamide added is calculated as follows: 0.4 parts of acrylamide is added for every 1 part of acrylic acid reduced.

[0008] Furthermore, the lignin-based adsorbent that is rapidly formed at low temperature comprises the following raw materials, measured by weight: 0.3 parts of sodium lignin sulfonate, 2-5 parts of acrylic acid, 0-1.2 parts of acrylamide, 1 part of zinc chloride, and 1 part of a strong oxidant.

[0009] Furthermore, the density of the sodium lignin sulfonate is 1.356 g / cm 3 ; The purity of the acrylic acid is 99%; The purity of the acrylamide is 99%; The content of zinc chloride is greater than 98wt%; The strong oxidant is sodium persulfate.

[0010] The present invention also provides a method for preparing a lignin-based adsorbent that can be rapidly formed at low temperature, comprising the following steps:

[0011] Add acrylamide to acrylic acid, stir well and then add zinc chloride, continue to stir well and then add sodium lignin sulfonate and a strong oxidant, react the obtained precursor solution at 25-30°C for 15-20 minutes, take out the sample and soak it in deionized water until the sample becomes translucent, and finally freeze-dry to obtain a lignin-based adsorbent that can be quickly formed at low temperature.

[0012] Furthermore, the acrylic acid is an acrylic acid solution with a neutralization degree of 70% prepared by using sodium hydroxide, and the content of the sodium hydroxide is greater than 96wt%.

[0013] The reaction principle of the present invention is as follows: the present invention uses sodium lignin sulfonate and acrylic acid as raw materials, and utilizes chelation to form a metal bridge between the sodium lignin sulfonate and acrylic acid to polymerize into a lignin-based adsorbent. Persulfate can initiate the polymerization of acrylic acid and acrylamide to generate polyacrylic acid and polyacrylamide. Adding Zn 2+ Later, Zn will directly form a metal bridge in the form of a metal bridge between polyacrylic acid polyacrylamide and sodium lignin sulfonate to bridge them together, thereby polymerizing to form a lignin-based adsorbent.

[0014] The present invention also provides a lignin-based adsorbent that can be quickly formed at low temperature, which is obtained by the above-mentioned preparation method.

[0015] The present invention also provides a use of a lignin-based adsorbent that is rapidly formed at low temperature in the treatment of heavy metal wastewater.

[0016] Furthermore, the heavy metals are manganese and zinc.

[0017] Compared with the prior art, the present invention has the following advantages and technical effects:

[0018] The present invention strictly controls the usage ratio of acrylic acid and acrylamide, and can prepare a lignin-based adsorbent using sodium lignin sulfonate as a raw material without adding a cross-linking agent. In addition, zinc chloride is added to the raw material, and zinc chloride forms a metal bridge under the chelation action of sodium lignin sulfonate and acrylic acid, thereby obtaining a new lignin-based adsorbent.

[0019] The method of the present invention is used to prepare a lignin-based adsorbent, which can be rapidly polymerized without adding a cross-linking agent, thereby preparing a green, rapidly formed lignin-based adsorbent with good mechanical properties and adsorption properties.

[0020] The lignin-based adsorbent of the present invention can be formed at a relatively low temperature in a short time. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0022] Figure 1 This is a schematic diagram of the reaction flow of an embodiment of the present invention;

[0023] Figure 2 The actual photos of the lignin-based adsorbent samples prepared in Examples 1-4 (from left to right are Example 1, Example 2, Example 3, and Example 4);

[0024] Figure 3 This is a viscosity test diagram of the lignin-based adsorbent sample prepared in Example 1;

[0025] Figure 4 is the toughness of the lignin-based adsorbent prepared in Examples 1-4;

[0026] Figure 5 The hardness of the lignin-based adsorbent prepared in Examples 1-4 (the weights of the two upper figures are 500 g, and the weights of the two lower figures are 100 g). DETAILED DESCRIPTION

[0027] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0028] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0029] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0030] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0031] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0032] In the prior art, the hydrogel adsorbent prepared with lignin as the matrix is ​​generally formed at 60-90°C, and the molding time is generally 1-3h. The preparation method of the present invention can effectively shorten the preparation time of the lignin-based hydrogel adsorbent, reduce the energy consumption of the reaction process, and at the same time significantly improve the adsorption amount of some heavy metal ions. The synthesis time of the prepared lignin-based hydrogel adsorbent is reduced from the original 1-3h to about 20min, and the molding temperature is reduced from the original 60-90°C to about 30°C, which greatly reduces the time and energy consumption required for the reaction.

[0033] The invention provides a lignin-based adsorbent that can be quickly formed at low temperature. The adsorbent comprises the following raw materials, measured by weight: 0.3 parts of sodium lignin sulfonate, 2-5 parts of acrylic acid, 0-1.2 parts of acrylamide, 1 part of zinc chloride and 1 part of a strong oxidant.

[0034] In the following preferred embodiments of the present invention, acrylic acid is preferably 4 or 5 parts. The formula is preferably 0.3 parts of sodium lignin sulfonate, 4 parts of acrylic acid, 0.4 parts of acrylamide, 1 part of zinc chloride, and 1 part of a strong oxidant. Or preferably 0.3 parts of sodium lignin sulfonate, 5 parts of acrylic acid, 0.4 parts of acrylamide, 1 part of zinc chloride, and 1 part of a strong oxidant.

[0035] The present invention also provides a method for preparing a lignin-based adsorbent that can be rapidly formed at low temperature, comprising the following steps:

[0036] Add acrylic acid to a beaker, add sodium hydroxide to neutralize to 70%, then add acrylamide, stir well and add zinc chloride, continue to stir well and add sodium lignin sulfonate and a strong oxidant, put the obtained precursor solution into an oven, react at 25-30°C for 15-20 minutes, take out the sample and soak it in deionized water until the sample becomes translucent, and finally freeze-dry to obtain a lignin-based adsorbent that can be quickly formed at low temperature.

[0037] The content of the sodium hydroxide is greater than 96 wt %.

[0038] The present invention also provides a low-temperature rapid-forming lignin-based adsorbent for use in heavy metal wastewater treatment. The adsorbed heavy metals include manganese and zinc.

[0039] In the following examples of the present invention, the density of sodium lignin sulfonate is 1.356 g / cm 3 The purity of acrylic acid is 99%; the purity of acrylamide is 99%; the content of zinc chloride is greater than 98wt%; the strong oxidant is sodium persulfate; the content of sodium hydroxide is greater than 96wt%.

[0040] Unless otherwise specified, the "room temperature" in the present invention is 25±2° C. Unless otherwise specified, the "parts" are calculated by mass.

[0041] The raw materials used in the following examples of the present invention are all commercially available.

[0042] The following examples serve as further illustrations of the technical solutions of the present invention.

[0043] Figure 1 The figure is a schematic diagram of the reaction flow of an embodiment of the present invention.

[0044] Example 1

[0045] Add 4 parts of acrylic acid into a beaker, add sodium hydroxide to obtain an acrylic acid solution with a neutralization degree of 70%, then add 0.4 parts of acrylamide, stir evenly, add 1 part of zinc chloride, continue to stir evenly, add 0.3 parts of sodium lignin sulfonate and 1 part of a strong oxidant, stir evenly to obtain a precursor solution; put the obtained precursor solution into a 30°C oven for 20 minutes, then take out the sample and soak it in deionized water until the sample becomes translucent, and finally freeze-dry to obtain a lignin-based adsorbent.

[0046] The lignin-based adsorbent prepared in this example was subjected to an adsorption test. The specific method was as follows: 2+ The concentration is 500mg / L, Zn 2+ The concentration is 500 mg / L, the volume is 50 ml, the dosage of the adsorbent is 0.02 g, and the temperature is kept constant at 35°C for 30 minutes.

[0047] Test results: for Mn 2+ The adsorption capacity can reach 495 mg / g for Zn 2+ The adsorption capacity can reach 323 mg / g.

[0048] Example 2

[0049] Same as Example 1, except that the amount of acrylamide added is 0 parts.

[0050] The lignin-based adsorbent prepared in this example was subjected to an adsorption test using the test method of Example 1. Test results: 2+ The adsorption capacity can reach 385mg / g for Zn 2+ The adsorption capacity can reach 278 mg / g.

[0051] Example 3

[0052] Same as Example 1, except that the added amount of acrylamide is 0.8 parts.

[0053] The lignin-based adsorbent prepared in this example was subjected to an adsorption test using the test method of Example 1. Test results: 2+ The adsorption capacity can reach 400mg / g for Zn 2+ The adsorption capacity can reach 293 mg / g.

[0054] Example 4

[0055] Same as Example 1, except that the amount of acrylamide added is 1.2 parts.

[0056] The lignin-based adsorbent prepared in this example was subjected to an adsorption test using the test method of Example 1. Test results: 2+ The adsorption capacity can reach 372mg / g for Zn2+ The adsorption capacity can reach 238mg / g.

[0057] Comparative Example 1

[0058] Same as Example 1, except that the obtained precursor solution was placed in an oven at 40° C. for 20 min.

[0059] Comparative Example 2

[0060] Same as Example 1, except that the mass of zinc chloride is replaced by manganese chloride.

[0061] Figure 2 The actual photos of the lignin-based adsorbent samples prepared in Examples 1-4 and Comparative Examples 1-2 show that a large number of bubbles appear on the surface of the lignin-based adsorbents prepared in Comparative Examples 1 and 2. The experimental results show that the lignin-based adsorbents prepared in the embodiments of the present invention can be formed in a short time at a relatively low temperature, but at high temperatures, the reaction between the substances is intensified due to the influence of temperature, thereby releasing a large amount of heat, destroying the gel structure, and failing to effectively prepare the lignin-based adsorbent.

[0062] Figure 3 This is a viscosity test diagram of the lignin-based adsorbent sample prepared in Example 1. As can be seen from the figure, the lignin-based adsorbent prepared in Example 1 has strong viscosity.

[0063] Performance Testing

[0064] In order to facilitate the recovery of the adsorbent, the adsorbent needs to have certain mechanical properties. Therefore, the hardness and toughness of the lignin-based adsorbents prepared in Examples 1-4 were simply tested. The results are as follows: Figure 4 , Figure 5 As shown in the figure, it can be seen that the lignin-based adsorbent prepared by the method of the present invention has certain strength and toughness.

[0065] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a lignin-based adsorbent that can be rapidly formed at low temperature, characterized in that: In parts by mass, it includes the following raw materials: 0.3 parts of sodium lignin sulfonate, 4 parts of acrylic acid, 0.4 parts of acrylamide, 1 part of zinc chloride, 1 part of strong oxidant; Or 0.3 parts of sodium lignin sulfonate, 4 parts of acrylic acid, 0 parts of acrylamide, 1 part of zinc chloride, and 1 part of a strong oxidant; Or 0.3 parts of sodium lignin sulfonate, 4 parts of acrylic acid, 0.8 parts of acrylamide, 1 part of zinc chloride, 1 part of strong oxidant; Or 0.3 parts of sodium lignin sulfonate, 4 parts of acrylic acid, 1.2 parts of acrylamide, 1 part of zinc chloride, 1 part of strong oxidant; Or 0.3 parts of sodium lignin sulfonate, 5 parts of acrylic acid, 0.4 parts of acrylamide, 1 part of zinc chloride, 1 part of strong oxidant; The method for preparing a lignin-based adsorbent that is rapidly formed at low temperature comprises the following steps: In acrylic acid, acrylamide is optionally added, and zinc chloride is added after stirring. After continuing to stir, sodium lignin sulfonate and a strong oxidant are added. The obtained precursor solution is reacted at 25-30°C for 15-20 minutes, and the sample is taken out and immersed in deionized water until the sample becomes translucent, and finally freeze-dried to obtain a lignin-based adsorbent that is quickly formed at low temperature; The acrylic acid is an acrylic acid solution with a neutralization degree of 70% prepared by using sodium hydroxide.

2. The method for preparing a lignin-based adsorbent for rapid prototyping at low temperature according to claim 1, characterized in that: The density of the sodium lignin sulfonate is 1.356 g / cm 3 ; The purity of the acrylic acid is 99%; The purity of the acrylamide is 99%; The content of zinc chloride is greater than 98wt%; The strong oxidant is sodium persulfate.

3. The method for preparing a lignin-based adsorbent for rapid prototyping at low temperature according to claim 1, characterized in that: The content of the sodium hydroxide is greater than 96wt%.

4. A lignin-based adsorbent that can be rapidly formed at low temperature, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 3.

5. Use of the low-temperature rapid-forming lignin-based adsorbent as claimed in claim 4 in the treatment of heavy metal wastewater.

6. The use according to claim 5, characterized in that: The heavy metals are manganese and zinc.

Citation Information

Patent Citations

  • Preparation method of loess-based polyacrylamide adsorbent

    CN104211856A

  • Lignin-based grafted modified porous adsorbing material and preparation method thereof

    CN104292496A

  • Preparation method and application of lignin-based polymer resin adsorbent

    CN110372832A

  • Preparation of lignin-based composite hydrogel and application of lignin-based composite hydrogel in heavy metal ion adsorption and luminescent materials

    CN113509907A

  • Method for preparing pH response type lignin-based adsorbent

    CN115999520A